2022
DOI: 10.1021/acs.energyfuels.2c02797
|View full text |Cite
|
Sign up to set email alerts
|

LiF-Modified SnO2 Electron Transport Layer Improves the Performance of Carbon-Based All-Inorganic CsPbIBr2 Perovskite Solar Cells

Abstract: SnO2 has gained wide attention because of its low synthesis temperature (approximately 150 °C), high electron mobility, and low manufacturing cost. However, the lattice mismatch at the SnO2/CsPbIBr2 interface and the oxygen vacancy leads to nonradiative recombination. Therefore, the key to improving the performance is to remove the defects between the SnO2 and the CsPbIBr2. In this paper, the first-principles calculation and experimental results show that the doping of LiF can enhance the conductivity of SnO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…PSCs are regarded as one of the most promising photovoltaic technologies because of the high light absorption coefficients and carrier mobility, long carrier diffusion length, and low manufacturing cost. , Although the PCEs of Pb-based PSCs have reached 25.7% recently, the commercialization is still limited by the toxicity of Pb, inherent wide band gap, and inferior stability . Replacing Pb with Sn at the B site is considered as an effective and simple solution to tackle the above-mentioned problems, enabling sustainable and clean perovskite photovoltaics.…”
Section: Fundamental Understanding Of Pb–sn Narrow-band-gap Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…PSCs are regarded as one of the most promising photovoltaic technologies because of the high light absorption coefficients and carrier mobility, long carrier diffusion length, and low manufacturing cost. , Although the PCEs of Pb-based PSCs have reached 25.7% recently, the commercialization is still limited by the toxicity of Pb, inherent wide band gap, and inferior stability . Replacing Pb with Sn at the B site is considered as an effective and simple solution to tackle the above-mentioned problems, enabling sustainable and clean perovskite photovoltaics.…”
Section: Fundamental Understanding Of Pb–sn Narrow-band-gap Perovskitesmentioning
confidence: 99%
“…It indicates that this bowing effect in the band gaps of Sn−Pb perovskites may be mainly related to the energy mismatch between 6s/6p orbitals of Pb and 5s/5p orbitals of Sn, while the spin−orbit coupling should not be the main cause of such a bowing effect. 47,104 Although the PCEs of Pb-based PSCs have reached 25.7% recently, the commercialization is still limited by the toxicity of Pb, inherent wide band gap, and inferior stability. 35 Replacing Pb with Sn at the B site is considered as an effective and simple solution to tackle the above-mentioned problems, enabling sustainable and clean perovskite photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature processed SnO 2 ETLs have been reported to deliver high device performance [14][15][16], even superior to that of their high-temperature processed counterparts [17,18]. Up to now, the main strategy for boosting the performance and stability of SnO 2 based devices has been to suppress energy loss within SnO 2 [19,20] or at the ETL/perovskite interface [21][22][23]. Doping is a direct and effective method of modifying the properties of SnO 2 , such as the conductivity and work function, which can facilitate electron extraction and transport [24].…”
Section: Introductionmentioning
confidence: 99%
“…14 However, SnO 2 films have inherent surface and bulk oxygen vacancies, which result in carrier recombination loss in the PSCs. 15,16 Besides, the SnO 2 ETL shows an energy level mismatch with the lead halide perovskite layer. 17,18 These imperfections inevitably result in a significant amount of open circuit voltage (V OC ) loss in the PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, SnO 2 films have inherent surface and bulk oxygen vacancies, which result in carrier recombination loss in the PSCs. , Besides, the SnO 2 ETL shows an energy level mismatch with the lead halide perovskite layer. , These imperfections inevitably result in a significant amount of open circuit voltage ( V OC ) loss in the PSCs. , An effective and facile way to adjust the energy level of semiconductor materials is element doping. , In n-type SnO 2 ETL, p-type doping may lower the density of the electron in the conduction band (CB) and tune the band alignment of the SnO 2 ETL . From the theoretical analysis, Duan et al revealed that the CB of the SnO 2 can be shifted to upward energy with the p-type doping .…”
Section: Introductionmentioning
confidence: 99%